Building on and tailoring to: Adapting a cancer caregiver psychoeducational intervention for rural settings - Erin E. Kent; Kelly R. Tan; Zev M. Nakamura; Jesse Kovacs; Mindy Gellin; Allison Deal; Eliza M. Park; Maija Reblin (Cancer Medicine)
Abstract Introduction Rural cancer caregivers experience obstacles in accessing services, obtaining respite, and ensuring their care recipients receive quality care. These challenges warrant opportunities to participate in evidence‐based behavioral intervention trials to fill support gaps. Adaptation to rural settings can facilitate appropriate fit, given higher caregiver service needs and unique challenges. We present findings from the adaptation process of a psychoeducational intervention designed to support cancer caregivers in rural settings. Methods We adapted Reblin's CARING intervention, designed for neuro‐oncology, to target caregivers of rural cancer patients across cancer sites. First, we conducted formative work to determine the unmet social and supportive care needs rural cancer caregivers faced. We used the Framework for Reporting Adaptations and Modifications to Evidence‐based Implementation Strategies (FRAME‐IS) to guide the modifications. To conduct the adaptation, we elicited feedback through qualitative interviews of seven caregivers and three cancer hospital staff and thematic analysis to inform intervention modifications. Our qualitative study was guided by the Consolidated Criteria for Reporting Qualitative Research (COREQ). Results Interviews revealed that service access was a pressing need, along with financial (e.g., treatment costs, employment challenges) and geographic barriers (e.g., distance to treatment, road conditions). We modified content, training, and context using the FRAME‐IS steps. Changes enhanced fit through the following adaptations: changes to social support domains, session content, interventionist training, resource offerings, screening and recruitment processes, and virtual delivery. Discussion Challenges to establishing successful psychosocial oncology interventions may be improved through participant‐centered approaches and implementation science. Additional systemic challenges, including lack of systematic documentation of caregivers, persist and may especially disadvantage under‐represented and underserved groups, such as rural dwellers. The enCompass intervention is undergoing ongoing single‐arm pilot of rural cancer patient/caregiver dyads targeting caregiver coping self‐efficacy and patient/caregiver distress (Clinical Trials #NCT05828927).